Emerging Developments on Nanocellulose as Liquid Crystals: A Biomimetic Approach - Thiruganasambanthan T.; Ilyas R.A.; Faiz Norrrahim M.N.; Muthu Kumar T.S.; Siengchin S.; Mohamad Misenan M.S.; Ahmad Farid M.A.; Mohd Nurazzi N.; Muhammad Asyraf M.R.; Syed Zakaria S.Z.; Rizal Razman M. (MDPI, 2023)
Anisotropic media; Anisotropy; Aspect ratio; Biomimetics; Chirality; Flat panel displays; Liquid crystals; Nanocellulose; Nanocrystals; Stereochemistry; Anisotropic medium; Bio-based; Biomimetic approaches; Crystalline order; Crystalline solids; High aspect ratio; Liquid-crystals; Natural biomass; One-dimensional; Solvent free; Cellulose derivatives; Anisotropy; Cellulose Derivatives; Characteristics; Engineering; Liquid Crystals; Medicine; Research; Stereochemistry